BETWEEN PASSING TIME AND ETERNITY: TADEUSZ GAJCY’S MIŁOŚĆ BEZ JUTRA (LOVE WITHOUT TOMORROW) IN THE CONTEXT OF GILBERT DURAND’S ANTHROPOLOGY OF THE IMAGINARY - Brasse, Rafał (Prace Polonistyczne, 2019)
Drawing inspiration from Gilbert Durand’s anthropology of the imaginary, the article offers an interpretation of Tadeusz Gajcy’s poem entitled Miłość bez jutra (Love without Tomorrow). It examines the paradigms of mythical time processed by imagination and the revival of images that have their roots in biblical cosmogony. Using the research method proposed by Durand, the author argues that the imaginary metaphorically transforms symbolic signs that are deeply rooted in history and culture, adjusting them to the personal situation of the dreaming speaker. In Miłość bez jutra the dream of carnal and spiritual fulfillment makes one experience time in relation to certain mythical objects, such as a plant, a book, or a chalice. The return to the mythical beginning, perceived as a refuge that guarantees spiritual revival, is associated with coming to terms with the inevitability of death. In this way, the palingenesis of eternal return (or, in other words, cosmic annihilation and rebirth) that is present in the Gajcy’s poem shapes the way of experiencing time. The author argues that the transformation and sacralization of mythical time in the poem are achieved through the image of a book (cloud) and a plant. Moreover, he shows that Gajcy’s allusions to the Genesis are intertwined with an apocalyptic vision in which various elements of the world are burnt, while the epiphanies of love and death are presented as a return to the state of original innocence and purity, experienced in symbolic projections.